2007
DOI: 10.1371/journal.ppat.0030196
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cells Targeted by Salmonella Type III Secretion In Vivo

Abstract: The type III secretion systems (TTSS) encoded in Salmonella pathogenicity island-1 and -2 (SPI-1 and -2) are virulence factors required for specific phases of Salmonella infection in animal hosts. However, the host cell types targeted by the TTSS have not been determined. To investigate this, we have constructed translational fusions between the ß-lactamase reporter and a broad array of TTSS effectors secreted via SPI-1, SPI-2, or both. Secretion of the fusion protein to a host cell was determined by cleavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(139 citation statements)
references
References 56 publications
(55 reference statements)
8
131
0
Order By: Relevance
“…Previous studies on translocation of effector proteins have shown that the FRET-based β-lactamase reporter assay is compatible with analysis by flow cytometry. [10][11][12] In the present report we show that our vacuolar rupture assay can also be analyzed by flow cytometry, which constitutes an important alternative and complementary read-out to microscopy-based data acquisition. Figure 1.…”
Section: Experimental Approachmentioning
confidence: 71%
See 1 more Smart Citation
“…Previous studies on translocation of effector proteins have shown that the FRET-based β-lactamase reporter assay is compatible with analysis by flow cytometry. [10][11][12] In the present report we show that our vacuolar rupture assay can also be analyzed by flow cytometry, which constitutes an important alternative and complementary read-out to microscopy-based data acquisition. Figure 1.…”
Section: Experimental Approachmentioning
confidence: 71%
“…7 Recently, this assay has been adapted to measure effector translocation or internalization of invasive bacteria in vitro and in vivo by creating β-lactamase fusion proteins with bacterial effectors. [8][9][10][11][12][13] Using Shigella invasion of host cells as a model system, we have extended these approaches by establishing a novel fluorescence microscopy assay that allows the study of vacuole rupture with high spatiotemporal precision (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…36 Moreover, both CD4 and CD8 T cells have been shown to internalize S. thyphimurium in infected mice. 37 The implication of Rab29 in IS assembly and T-cell activation suggests a potential novel target for immune evasion by Salmonella involving the protease GtgE. By preventing the delivery to the IS of endosomal TCRs, which requires Rab29, in infected T cells, GtgE would be expected to effectively suppress the long-lasting signaling required for T-cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Y. enterocolitica is known to disseminate, among other locations, to the spleen, where they replicate predominately extracellularly and form microcolonies consisting primarily of extracellular residing Yersinia-bacteria and neutrophils (66). In contrast, S. Typhimuruim is an intracellular living pathogen that has been recently shown to specifically target splenic neutrophils and to survive and replicate inside them (67). However, despite the different life styles of Yersinia and Salmonella, Ly6G + neutrophils represented also a major IL-10-producing population in the spleen of Salmonella-infected ITIB mice.…”
Section: Discussionmentioning
confidence: 99%